ANALISIS LQ, SHIFT SHARE, DAN PROYEKSI PRODUK DOMESTIK REGIONAL BRUTO JAWA TIMUR 2017 - Lumadya, Adi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2017)
The purpose of this study are: (1). Analyzing East Java GDRP sectors with GDP to determine base sectors; (2). Analyzing East Java GDRP sectors with GDP to determine the value National Share, Proportional Shift and Differential Shift; (3). To estimate East Java GDRP based on GDP projected. Analysis tools: (1). Location Quotient (LQ) and (2). Shift-share Analysis Result analysis: (A). LQ> 1, there are five base sectors are: Industri Pengolahan; Pengadaan Air, Pengolahan Limbah, Sampah; Perdag. Besar dan Retail; Reparasi Mobil dan Motor; Akomodasi dan Makan Minum; Informasi dan Komunikasi. (B). The biggest share is Industri Pengolahan by 15.27%, while the smallest is Pengadaan Air, Pengolahan Limbah, Sampah by 0.05%. (C). Proportional Shift have four sectors are negative. (D). Shift Differential have eleven sectors are negative. (E). Projected East Java Gross Domestic Regional Product in 2017 are 1517.49 billion Rupiah.